Dataset: Exploring the Landscape of Cyber Harassment: A Data-driven Approach to Understanding the Legal Framework - Asrul Maulana; Mochammad Tanzil Multazam (International Consortium of Education and Culture Research Studies, 2022)
This research focuses on the search for articles and literature reviews on cyber harassment. The search was conducted using Lens.org, a reliable indexing agency, by using keywords such as Cyber law and Cyber Harassment. Three keywords were selected and entered into the 'edit search' feature, and the search was filtered by selecting the law category in the subject matter and choosing journal articles as the document type. The data was exported in both CSV and BibTeX formats, and a screenshot was taken of the available data graphs. The goal of this research is to collect data on cyber harassment and its legal implications. The method involved searching scholarly works using specific keywords and filtering the results based on subject matter and document type. The results obtained are valuable as they provide a comprehensive understanding of the current state of cyber harassment and its legal implications. Highlights: Filtering through specific categories and document types is an effective way to obtain relevant literature on cyber harassment. The ten articles found provide a diverse range of topics related to cyber harassment, from the impact of technology on online sexual harassment to the legal response to cyberbullying. These articles offer valuable insights for future research and can be used as references for scholars studying cyber harassment.